Reversal by NPY, PYY and 3-36 molecular forms of NPY and PYY of intracisternal CRF-induced inhibition of gastric acid secretion in rats. - Gué, M. (1996)
1. The Y receptor subtype involved in the antagonism by neuropeptide Y (NPY) of intracisternal corticotropin-releasing factor (CRF)-induced inhibition of gastric acid secretion was studied in urethane-anaesthetized rats by use of peptides with various selectivity for Y1, Y2 and Y3 subtypes: NPY, a Y1, Y2 and Y3 agonist, peptide YY (PYY), a Y1 and Y2 agonist, [Leu31, Pro34]-NPY, a Y1 and Y3 agonist, NPY(3-36) and PYY(3-36), highly selective Y2 agonists and NPY(13-36) a weak Y2 and Y3 agonist. Peptides were injected intracisternally 10 min before intracisternal injection of CRF (10 micrograms) and gastric acid secretion was measured by the flushed technique for 1 h before and 2 h after pentagastrin-(10 micrograms kg-1 h-1, i.v.) infusion which started 10 min after CRF injection. 2. Intracisternal injection of CRF (10 micrograms) inhibited by 56% gastric acid secretion stimulated by pentagastrin. Intracisternal injection of NPY and PYY (0.1-0.5 microgram) did not influence the acid response to pentagastrin but blocked CRF-induced inhibition of pentagastrin-stimulated acid secretion. NPY(3-36) (0.5 microgram) and PYY(3-36) (0.25 and 0.5 microgram) also completely blocked the inhibitory action of CRF on pentagastrin-stimulated acid secretion. 3. [Leu31, Pro34]-NPY (0.5-5 micrograms) and NPY(13-36) (0.5-5 micrograms) injected intracisternally did not modify gastric acid secretion induced by pentagastrin or CRF inhibitory action. 4. The sigma antagonist, BMY 14802 (1 mg kg-1, s.c.) did not influence the acid response to pentagastrin but prevented the antagonism by PYY(3-36) (0.5 microgram) of the CRF antisecretory effect. 5. These results show that both PYY and NPY and the 3-36 forms of PYY and NPY are equipotent in blocking central CRF-induced inhibition of pentagastrin-stimulated gastric acid secretion. The structure-activity profile suggests a mediation through Y2 receptor subtype and the involvement of sigma binding sites.